New abolition, criminology and a critical carceral studies. (October 2017) - Brown, Michelle; Schept, Judah
Criminology has been slow to open up a conversation about decarceration and abolition in comparison with other disciplines, including history, geography, and gender, race, and critical ethnic studies. Scholars from these areas and actors on the ground—close up to confinement—have done most of the organizing against mass incarceration and theorizing of alternative possibilities. Why those experiences—and the theoretical traditions that inform their work—have been less recognized and developed in criminology is of pivotal concern as more criminologists move forward with the political project of decarceration. The extent to which criminology can sustain an alternative or abolitionist politics remains an open question. Amid growing conversations about decarceration and shifting rhetorics on punishment, we address some of the obstacles that limit criminology as a site from which to engage the abolitionist project, asking where criminologists might turn for interventionist models that move away from imprisonment and the violence of the carceral state. In this article, we advocate for and discuss the contours of critical carceral studies, a growing interdisciplinary movement for engaged scholarly and activist production against the carceral state. We discuss the imperatives for criminological engagement with critical carceral studies and sketch some of the terrain on which the discipline can contribute to the project, including important work to counter criminological discourses and knowledge production that reify and reproduce carceral logics and practices.